2017
DOI: 10.1038/cddis.2016.354
|View full text |Cite
|
Sign up to set email alerts
|

Berberine-sonodynamic therapy induces autophagy and lipid unloading in macrophage

Abstract: Impaired autophagy in macrophages accompanies the progression of atherosclerosis and contributes to lipid loading in plaques and ineffective lipid degradation. Therefore, evoking autophagy and its associated cholesterol efflux may provide a therapeutic treatment for atherosclerosis. In the present study, berberine-mediated sonodynamic therapy (BBR-SDT) was used to induce autophagy and cholesterol efflux in THP-1 macrophages and derived foam cells. Following BBR-SDT, autophagy was increased in the macrophages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…Torin1, a potent inhibitor of mTORC1/2, is generally applied as an autophagy inducer (Min et al, 2018). Hydroxychloroquine sulfate (CQ), an acidification inhibitor that impedes lysosome-mediated degradation, can accumulate autophagosomes and suppress autophagic flux (Kou et al, 2017). Here, we discovered that in both Torin1-treated cells and HTNV-infected cells of the 6 hpi group, most LC3-positive autophagic vacuoles were red (Figure 2A), indicating that these stimuli trigger complete autophagy flux.…”
Section: (Legend On Next Page)mentioning
confidence: 90%
“…Torin1, a potent inhibitor of mTORC1/2, is generally applied as an autophagy inducer (Min et al, 2018). Hydroxychloroquine sulfate (CQ), an acidification inhibitor that impedes lysosome-mediated degradation, can accumulate autophagosomes and suppress autophagic flux (Kou et al, 2017). Here, we discovered that in both Torin1-treated cells and HTNV-infected cells of the 6 hpi group, most LC3-positive autophagic vacuoles were red (Figure 2A), indicating that these stimuli trigger complete autophagy flux.…”
Section: (Legend On Next Page)mentioning
confidence: 90%
“…It has been demonstrated that at the early stage of pulmonary fibrosis, Brb is more beneficial and has more preventive effects, whereas at the late stage, the efficacy of Brb is lower and in both stages, Brb increases autophagy. Brb can be used as a potential therapy for atherosclerosis, as well (Kou et al, 2017). The Brbsonodynamic therapy elevates the production of reactive oxygen and, subsequently, inhibits the activation of the Nod-like receptor family pyrin domain containing 3 (NFRL3) inflammasome.…”
Section: The Role Of Brb In Autophagy Inductionmentioning
confidence: 99%
“…The siRNA sequences were as follows: negative control (NC) siRNA: 5 0 -UUCUCCGAACGUGUCACGUTT-3 0 , 3 0 -ACGUGACACGU UCGGAGAATT-5 0 ; Beclin-1 siRNA 1: 5 0 -GGUCUAAGACGUC CAACAATT-3 0 , 3 0 -UUGUUGGACGUCUUAGACCTT-5 0 ; Beclin-1 siRNA 2: 5 0 -GGAGCCAUUUAUUGAAACUTT-3 0 , 3 0 -AGUUUCA AUAAAUGGCUCCTT-5 0 ; Beclin-1 siRNA 3: 5 0 -GCUGCCGUUA UACUGUUCUTT-3 0 , 3 0 -AGAACAGUAUAACGGCAGCTT-5 0 ; and Atg5 siRNA: 5 0 -GCUUCGAGAUGUGUGGUUUTT-3 0 , 3 0 -GCUUCG AGAUGUGUGGUUUTT-5 0 . Atg5 siRNA was chosen according to a previous study [19].…”
Section: Rna Interferencementioning
confidence: 99%